Demand and capacity planning in the emergency department: how to do it. Issue 2 (28th October 2010) - Higginson, I; Whyatt, J; Silvester, K
Abstract : Background: Unless emergency departments have adequate capacity to meet demand, they will fail to meet clinical and performance standards and will be operating in the 'coping zone'. This carries risks both for staff and patients. Methods: As part of a quality improvement programme, the authors undertook an in-depth analysis of demand and capacity for an emergency department in the UK. The paper describes this rigorous approach to capacity planning, which draws on techniques from other industries. Discussion and conclusions: Proper capacity planning is vital, but is often poorly done. Planning using aggregated data will lead to inadequate capacity. Understanding demand, and particularly the variation in that demand, is critical to success. Analysis of emergency department demand and capacity is the first step towards effective workforce planning and process redesign.